Azospirillum brasilense and organomineral fertilizer co-inoculated with Bradyrhizobium japonicumon oxidative stress in soybean - Fernanda Barros; Reginaldo de Camargo; Regina Maria Lana; Miguel Henrique Franco; Mayara Cristiana Stanger; Vanderley José Pereira; Ernane Lemes (International Journal of Recycling of Organic Waste in Agriculture, 2022)
Purpose Nitrogen-fixing bacteria (NFB) are essential for biologically fixing nitrogen in natural and soybean crop systems. The use of organomineral fertilizers is a promising crop management tool made from the mixing of an organic source and mineral fertilizers. This study evaluated the efficacy of an organomineral fertilizer (sewage sludge-based) as a carrier for the Azospirillum brasilense inoculation and the influence of A. brasilense plus Bradyrhizobium japonicum on the soybean antioxidant metabolism.Method The experiment was performed under greenhouse conditions. The soybean cultivar (AS 3680 IPRO) was evaluated in a 4×2(+1) factorial scheme, corresponding to four doses of A. brasilense [0, 100, 200, 300 mL ha-1 (2x108 viable cells mL-1) per 50 kg-1 of soybean seeds], with or without B. japonicum [100 mL ha-1 (5x109 viable cells mL-1) per 50 kg-1 of soybean seeds], and a control treatment (without inoculants or fertilizers). Soybean antioxidant metabolism (enzymes, oxidative processes, proline amino acid) was evaluated in different plant stages.Results The seed inoculation with A. brasilense via organomineral fertilizer enhanced the soybean plant protection factors. Plant protection to stresses happened mainly by reductions in the superoxide dismutase activity, lipid peroxidation, and hydrogen peroxide concentration. The co-inoculation of A. brasilense with B. japonicum enhanced the proline activity at the V3 and R5 soybean phenological stage compared to A. brasilense inoculated alone.Conclusion The studied organomineral fertilizer is an efficient inoculant carrier for A. brasilense in soybean plants via seed treatment. The protective results observed for A. brasilense were improved when co-inoculated with B. japonicum.